The Algerian crime novel between adventure and experimentation"Kharij elsaytara" by Abdellatif Ould Abdallah as a model (مجلة إحالات, 2026)
The detective novel has worked to exploit the components of the modern artistic novel, both at thelevel of form and content. It has become based on a fantasy framed by the cases of investigating themysterious crime Le crime mystérieux, and the investigator's decoding of the mysteries of the casethrough the L'Enquête investigation process and follow-up, in addition to relying on a suspenseful plotthat mixes and overlaps with the rest of the main pillars such as the criminal, the victim, the suspect, themisleading elements, and the solution... Etc. Despite the novelty of the detective novel, and its greatpopularity, its share of attention in Arabic literature in general, and Algerian literature in particular, interms of creativity, history, criticism and rooting, is almost non-existent. Based on this, the subject of this research paper was determined in tracing the stage of experimentation that the Algerian police narrator knew in the novel Out of Control by Abd al-Latif Ould Abd Allah, as well as an investigation of the features of the police novel and its obstacles in Arabicliterature, and this is what we will see in the book The Detective Novel: An Examination of Theory,Historical Origins, Artistic Characteristics and its Impact on the Arabic Novel by Abdelkader Cherchar.